2015
DOI: 10.1007/s40688-015-0059-5
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Strategies in European American and Hong Kong Chinese Middle School Children

Abstract: This study explored emotion regulation strategies in middle school European American (N=54) and Hong Kong Chinese (N=89) children. Children were presented with scenarios describing a fictitious girl/boy who encountered situations eliciting sadness, anger, and fear. Based on Gross' theory (1998), the survey of emotion regulation strategies was designed to study children's perceived effectiveness of emotion regulation strategies including deep breathing, positive distraction, situation avoidance, talking to some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In addition, a total of n=2 studies looked into the parental, caregivers, or environmental influence on the children's application of emotion regulation strategies (Liu et al 2019, Schoppmann et al 2022. Also, n=4 studies aimed to make a comparison of the usage of emotion regulation strategies among children with different age groups and in a different context of family, peers, school, and behaviours (Wan & Savina 2015, Lopesz-Perez et al 2016, Cai et al 2020, Wang & Barrett 2020.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a total of n=2 studies looked into the parental, caregivers, or environmental influence on the children's application of emotion regulation strategies (Liu et al 2019, Schoppmann et al 2022. Also, n=4 studies aimed to make a comparison of the usage of emotion regulation strategies among children with different age groups and in a different context of family, peers, school, and behaviours (Wan & Savina 2015, Lopesz-Perez et al 2016, Cai et al 2020, Wang & Barrett 2020.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all articles had an even number of strategies, as few studies mentioned more than one strategy, while some studies interpreted the strategies by giving situational examples, explaining strategies sub-categories and even synonymous terms of the strategies. In correlation, n=10 articles focused on more than one strategy (Wan & Savina 2015, Lopez-Perez et al 2016, Rao & Gibson 2018, Parsafar et al 2019, Atkinson et al 2020, Cai et al 2020, Hipson et al 2019 Attachment assessment at two years has portrayed significant results even though it provides an indirect predictor of social regulation for children aged 10 to 12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to cultural differences in the valuing and meaning of positive and negative emotions, Asians tend not to savor positive emotions, and are less likely to down-regulate negative emotion while European Americans prefer not to dampen positive emotions and are more likely to regulate emotion hedonically in experimental and experiential settings ( Miyamoto and Ma, 2011 ; Miyamoto et al, 2014 ). Wan and Savina (2015) compared preferred emotion regulation strategies in US and Hong Kong Chinese public school children. They observed that US children endorsed positive distraction and talking to someone to a greater extent than the comparison group, while Chinese (but not US) children endorsed deep breathing as a fear regulation strategy.…”
Section: Introductionmentioning
confidence: 99%